Hydrothermal Synthesis and Structural Characterization of a Three-Dimensional Coordination Polymer on Ag(I). Issue 5 (3rd May 2016) - Chen, Qi; Lun, Hui-Jie; Li, Yong-Hong; Li, Shu; Li, Bei-Bei; Zhang, Xu-Dong; Li, Ya-Min
Abstract : A new coordination polymer [Ag3 (1, 2, 4-btc)]n (1 ) (1, 2, 4-H3 btc = 1, 2, 4-benzenetricarboxylate) has been synthesized by hydrothermal method and characterized by X-ray single crystal diffraction, elemental analysis, IR spectrum, and TGA. Compound1 exhibits a 3D network consisting of the 2D layer connected by the ligand 1, 2, 4-btc 3−, which adopts a new coordination mode. Moreover, blue fluorescence at 480 nm emission was observed under 320 nm excitation.